Kesiapan Sumber Daya Manusia dalam Menghadapi Implementasi Teknologi Digital: Studi Kebutuhan Pelatihan dan Pengembangan Kompetensi - Fitria Marisya; Rosma Novianti; Ahmad Yani Kosali; M Bambang Purwanto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The rapid digital transformation requires human resources (HR) to adapt to various new technologies in the work environment. This research aims to analyze the level of readiness of human resources in facing the implementation of digital technology, identify the digital competencies needed, and formulate relevant training strategies based on actual needs. The research method employed was a descriptive, quantitative approach using a survey of 120 respondents from the service and public administration sectors. The results show that HR readiness levels vary, with younger generations and operational job positions exhibiting higher readiness than senior generations and top-level management. The most essential digital competencies include basic digital literacy, data analysis skills, software utilization for work, cybersecurity, and digital communication. The primary implication of these findings is the need for initial competency mapping and the implementation of need-based training to address the challenges of digital transformation effectively. The study also identified implementation barriers, including budget constraints, resistance to change, and lack of top management support. These findings make a crucial contribution to the development of adaptive and sustainable HR strategies in the digital era.